Consensus Control of Mobile Agents with Obstacle Avoidance using Collision Cone Approach - Akkaya, Sirin; Akbati, Onur; Ergenc, Ali Fuat (IEEE, 2018)
In this study, a cooperative control problem with obstacle avoidance for a team mobile agent system is investigated. The agents are modelled with double integrator dynamics considering the center coordinates in 2D space. The underlying topology of the focused system is captured by an undirected graph. Firstly, basic consensus controller structures are explained. Then obstacle avoidance problem which is based on collision cone approach is examined. Finally, both controller algorithms are combined and simulated with using second-order agent model. Simulation studies have been conducted with MATLAB program. The obstacle is selected a circle stationary object. The results show that the agents use the collision avoidance algorithm to prevent obstacle and consensus algorithm to reach consensus point after passing the obstacle.
Keywords: multi agent; consensus; obstacle avoidance; cooperative control; collision cone approach; MULTIAGENT SYSTEMS; COORDINATION; Automation & Control Systems; Computer Science; Engineering